Community sports fields and atmospheric climate impacts: Australian and Canadian perspectives. Issue 4 (4th July 2021) - Dingle, Greg; Mallen, Cheryl
ABSTRACT: Purpose: This paper presents a study of atmospheric climate impacts on community-level sports clubs' (CLSC) in Australia and Canada, their vulnerability and resilience, and organisational responses. Design/Methods: A qualitative methodology was used with a multiple case research design. Data (interviews, documents) was collected from a sample of 23 CLSC organisations managing grass turf sport fields exposed to climatic extremes in temperate regions of both countries. Findings: CLSCs in both nations experienced vulnerability to climate impacts. Direct damage to playing fields resulted from extreme climate events. Indirect impacts include higher injury risks, interrupted and/or cancelled competitions, insurance risks, plus higher operating and capital costs. Adapted management was evident for water resources, playing turf, and organisational policies. Practical Implications: Provides insights into the changing practice of sport management at the community-level. Research Contribution: The results challenge the assumption that climate is a static and benign resource for sport. This study demonstrates impacts of climate extremes on sport in the northern and southern hemispheres, the potential for adapting sport management practices, and developing resilience.